Auto rain wiper system performance due to fundamental climate factors in Bandar Tun Abdul Razak, Jengka / Mohd Khairul Mohd Yackup - Mohd Yackup, Mohd Khairul (Faculty of Applied Sciences, 2018)
This projects aims is to develop the auto wiper system by using programmable software. This system functions through the combination of the hardware and software. This system is called auto wiper performance due to climate factors . using a rain sensor and Arduino microcontroller system to test the effectiveness of this system. The advantage of this project was to help users to use the wiper automatically when the sensor detects raindrops. A driver doesn't need to tum on or tum off the wiper control stalk. This system will reduce driver distraction while driving and will function automatically when the raindrops. Rains sensor was used to sense the raindrop or moisture when it hitting on sensor. Therefore, the function of the system is to measure the rain intensity using measuring cylinder and LCD display. The main objectives of this project are to upgrade the older car wiper system and to measure the intensity of rainfall. The speed of the auto wiper is based on the amount of rainfall detected by the rain sensor. When the rain is heavy, wiper will move fast. At the medium rain, wiper will move at medium speed and at the lower rain condition wiper will move slow. The mechanical function is used to control the motor system. By using this system, user doesn't control the wiper system manually and this system function using controller system.